Utility of Infrared Technology in Minimally Invasive Procedures: A Novel Strategy to Identify a Esophagobronchial Fistula via Thoracoscopy - Isabel González-Barba; Ana Laín; Laura García; Carlos Giné; Manuel López (Elsevier, 2023)
Esophagobronchial or esophagopulmonary fistulas are complications after esophageal atresia/tracheoesophageal fistula (EA/TEF) repair. Postoperative scarring and recurrent infections render surgical treatment a potentially hazardous undertaking.This report describes the use of infrared (IR) technology to locate and safely dissect a esophagobronchial fistula in a 11-year-old female with a history of EA/TEF. The patient, who had initially undergone primary repair via thoracotomy, was diagnosed with a late tracheoesophageal fistula (TEF) recurrence at the age of 6 after several pulmonary infections and was subjected to a left thoracoscopy with successful closure of the TEF.  Despite both surgical procedures, she presented ongoing respiratory symptoms for several years and was referred to our center as an 11-year-old, where further examinations revealed the presence of a esophagobronchial fistula involving the right upper bronchus. After an unsuccessful attempt at endoscopic closure, surgical treatment via right thoracoscopy was planned. Initially, an endoscopic examination was performed, to catheterize the fistula tract in the mid-thoracic esophagus with the infrared probe. Subsequently, right thoracoscopy was performed in the prone position using four 5 mm trocars. Guided by the IR signal, the fistula tract was easily identified and dissected. Fistula closure was achieved using a 5 mm stapler. The staple line was reinforced with a pleural flap and a right thoracic tube was inserted. The patient was discharged after a four-day hospital stay, without complications. The patient remains asymptomatic to date and has returned to her native Ukraine.